2018
DOI: 10.1016/j.neuron.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a Spatial Map across the Hippocampal-Lateral Septal Circuit

Abstract: The hippocampus constructs a map of the environment. How this "cognitive map" is utilized by other brain regions to guide behavior remains unexplored. To examine how neuronal firing patterns in the hippocampus are transmitted and transformed, we recorded neurons in its principal subcortical target, the lateral septum (LS). We observed that LS neurons carry reliable spatial information in the phase of action potentials, relative to hippocampal theta oscillations, while the firing rates of LS neurons remained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(137 citation statements)
references
References 65 publications
5
129
3
Order By: Relevance
“…The preserved place cell activity after gabazine injections demonstrates that the neural computation of self‐localization information occurs independently of the strength of the hippocampal theta rhythm. However, the theta rhythmic organization of hippocampal output may be critical for its ability to communicate to downstream structures and influence ongoing behavior (Benchenane et al, ; Hyman, Zilli, Paley, & Hasselmo, ; Tabuchi et al, ; Tingley & Buzsaki, ). To directly assess navigation abilities following septal injections, we trained rats in a place accuracy task where the rats were required to pause in a specific goal area in the recording arena to trigger the release of a sugar pellet from an overhead pellet feeder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preserved place cell activity after gabazine injections demonstrates that the neural computation of self‐localization information occurs independently of the strength of the hippocampal theta rhythm. However, the theta rhythmic organization of hippocampal output may be critical for its ability to communicate to downstream structures and influence ongoing behavior (Benchenane et al, ; Hyman, Zilli, Paley, & Hasselmo, ; Tabuchi et al, ; Tingley & Buzsaki, ). To directly assess navigation abilities following septal injections, we trained rats in a place accuracy task where the rats were required to pause in a specific goal area in the recording arena to trigger the release of a sugar pellet from an overhead pellet feeder.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, since overall grid cell activity is also affected by septal inactivation, septal gabazine injections could be used in future studies to more directly test the role of theta rhythm in producing grid cell spatial firing patterns. However, recent work has demonstrated that spatial information in hippocampal output structures explicitly depends on phase coding relative to hippocampal theta (Tingley & Buzsaki, ). Thus, the coherent theta rhythm, coordinating activity across hippocampus and associated downstream regions, may form a channel for the broadcast of spatial information that is critically necessary to convert spatial codes to adaptive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such models, oscillatory modulation of spike trains occurs in such a way that position information is conveyed by between‐cell spike intervals (i.e., spike correlations), rather than within‐cell spike intervals (i.e., firing rates). Recent evidence suggests that neural populations in the lateral septum may utilize this type of oscillatory interference code for the rat's position (Tingley & Buzsaki, ). Simulations presented below show that when an oscillatory interference code is constructed from simulated theta cells, position information can be recovered from theta cell co‐firing rates using a sigma‐chi decoding process similar to that used above for recovering velocity information from HD cell or grid cell co‐firing rates, and velocity information can be recovered from theta cell firing rates using the same sigma decoding process that was used above to recover position information from HD cell or grid cell firing rates.…”
Section: Resultsmentioning
confidence: 99%
“…Position‐tuned neurons (such as place and grid cells) exhibit oscillatory modulation of their spike trains by theta rhythm. Information about the animal's position can be decoded not only from the firing rates of these neurons (Wilson & McNaughton, ), but also from the phases at which spikes occur relative to theta rhythm in the local field potential (Climer, Newman, & Hasselmo, ; Hafting, Fyhn, Bonnevie, Moser, & Moser, ; Jeewajee et al, ; Jensen & Lisman, ; O'Keefe & Recce, ; Skaggs, McNaughton, Wilson, & Barnes, ; Tingley & Buzsaki, ). Hence, spatially tuned neurons can encode the animal's position in two different ways: in their firing rates and firing phases.…”
Section: Introductionmentioning
confidence: 99%